Compliance Audit Sebagai Alat Untuk Mendorong Tercapainya Tujuan Organisasi (Studi kasus pada Hotel The 101 Suryakencana Bogor) - Khairunnisa, Nova; Yuliandi, Yuliandi (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
The purpose of this study was to determine the implementation of compliance audit at The 101 Suryakancana Bogor Hotel, knowing the achievement of Bogor 101 The Hotel Suryakancana through a predetermined procedural policy, and knowing whether compliance audit is influential in achieving the 101 The Suryakancana Bogor Hotel goal. The method used in this study is a qualitative descriptive method. This method aims to understand the phenomena that occur based on existing theories compared to practice when conducting research in the field. The author explains the implementation of compliance audit, achievement of organizational objectives, and compliance audit as a tool to achieve organizational goals. The results showed that the implementation of compliance audit at The 1O1 Suryakencana Hotel Bogor was conducted through five stages: audit planning, audit testing and evaluation, reporting of audit findings, recommendations and monitoring and follow-up. Audit Compliance at The 1O1 Suryakencana Bogor Hotel can be said to be "Good" because it has an average value of 5 in period I and period II auditing and does not experience a change in criteria. In its achievement and service goals, The 1O1 Suryakencana Bogor Hotel has provisions and standards or SOP (Standard Operating Procedures) and rules regarding grooming for employees to provide a good image to guests staying at the hotel. The implementation of grooming and SOP regarding the arrival of guests has been carried out well, but there are several stages and rules that are not obeyed by the relevant department staff, so the stages and rules cannot be fully achieved. The implementation of compliance audit at The 1O1 Suryakencana Hotel Bogor has been running well, especially in hotel services, evidenced by reduced audit findings in period I and period II and findings between period I and period II are not the same and not repeated. Additionally, hotel revenue receipts after the first audit period experienced an increase in the following month Achievement of the objectives of the hotel is increasingly achieved. Satisfaction and comfort of guests or customers are also fulfilled supported by the image provided by the hotel through its employees and compliance with applicable procedures.